Glutamatergic antagonism in the NTS decreases post-inspiratory drive and changes phrenic and sympathetic coupling during chemoreflex activation - Costa Silva, J. H.; Machado, Benedito Honório; Zoccal, Daniel Breseghello [UNESP] (American Physiological Society, 2010)
For a better understanding of the processing at the nucleus tractus solitarius (NTS) level of the autonomic and respiratory responses to peripheral chemoreceptor activation, herein we evaluated the role of glutamatergic neurotransmission in the intermediate (iNTS) and caudal NTS (cNTS) on baseline respiratory parameters and on chemoreflex-evoked responses using the in situ working heart-brain stem preparation (WHBP). The activities of phrenic (PND), cervical vagus (cVNA), and thoracic sympathetic (tSNA) nerves were recorded before and after bilateral microinjections of kynurenic acid (Kyn, 5 nmol/20 nl) into iNTS, cNTS, or both simultaneously. In WHBP, baseline sympathetic discharge markedly correlated with phrenic bursts (inspiration). However, most of sympathoexcitation elicited by chemoreflex activation occurred during expiration. Kyn microinjected into iNTS or into cNTS decreased the postinspiratory component of cVNA and increased the duration and frequency of PND. Kyn into iNTS produced no changes in sympathoexcitatory and tachypneic responses to peripheral chemoreflex activation, whereas into cNTS, a reduction of the sympathoexcitation, but not of the tachypnea, was observed. The pattern of phrenic and sympathetic coupling during the chemoreflex activation was an inspiratory-related rather than an expiratory-related sympathoexcitation. Kyn simultaneously into iNTS and cNTS produced a greater decrease in postinspiratory component of cVNA and increase in frequency and duration of PND and abolished the respiratory and autonomic responses to chemoreflex activation. The data show that glutamatergic neurotransmission in the iNTS and cNTS plays a tonic role on the baseline respiratory rhythm, contributes to the postinspiratory activity, and is essential to expiratory-related sympathoexcitation observed during chemoreflex activation.